REKONSTRUKSI IDENTITAS ZULQARNAIN: ANALISIS TAFSIR KOMPARATIF ATAS PERBEDAAN PENDAPAT ULAMA TAFSIR DAN HADIS DALAM QS AL-KAHFI 83–98 - Nasrul Fatah (Jurnal Payung Sekaki : Kajian Keislaman, 2026)
The narrative of Dhul-Qarnain in QS Al-Kahf verses 83, 86, and 94 has long invited debate among exegetes and historians regarding his historical identity, with Alexander the Great and Cyrus the Great being the two most frequently proposed figures. This study aims to map and critically analyze the views of exegetical and hadith scholars on the identity of Dhul-Qarnain, and to examine the compatibility between the characteristics described in the Qur'an and hadith with the historical records of both figures. This is a qualitative library research employing a comparative tafsir (muqaran) approach, drawing on primary data from the verses of Al-Kahf and related hadith, as well as secondary data from classical and contemporary tafsir works. The findings show that the Qur'an mentions eleven principal characteristics of Dhul-Qarnain, while the hadith affirm four additional traits, including his meeting with Prophet Ibrahim. A comparison of these characteristics with the historical records of Alexander and Cyrus indicates that Cyrus more closely matches the religious character described, whereas Alexander is historically associated with polytheism. Nevertheless, Ibn Hajar al-'Asqalani's argument that Dhul-Qarnain was a distinct figure contemporaneous with Prophet Ibrahim—preceding both Alexander and Cyrus by many centuries—is judged methodologically stronger, as it rests on traceable chains of transmission. This study contributes to strengthening the comparative tafsir method for examining historical figures in the Qur'an and offers a textual-contextual verification framework applicable to the study of other Qur'anic figures.